Communication competence among managers in government sectors in Perak Tengah District, Perak / Nor Farhana Mohd Azmi ... [et al.] - Mohd Azmi, Nor Farhana; Abd Karim, Zatul Himmah; Anual, Norazlan; Hashim, Norhafiza (2014)
This study focuses on factors that contribute to communication competence that includes knowledge, skills and behavior. Besides that this study also aims to identify whether the respondents apply Communication Competency at their workplace. Communication competence is the demonstration of communication knowledge through the appropriate use of communication skills (Lailawati Mohd Salleh, 2011). The respondents are managers working at Government sectors, at the District of Perak Tengah which consist of 17 government organizations. These respondents were chosen because the researchers want to understand the managers’ communication competencies as a personal trait, as well as, organizational need and excellence. The study has revealed that majority of the respondents did apply knowledge, skill and behavior in their communication especially in dealing with clients, subordinates and their staff.